3-D High-Resolution ISAR Imaging for Noncooperative Air Targets - Marcin Kamil Baczyk; Piotr Samczynski; Jedrzej Drozdowicz; Maciej Wielgo; Jakub Sobolewski; Marek Ciesielski; Jakub Julczyk; Krzysztof Stasiak; Grzegorz Pietrzykowski; Karol Abratkiewicz; Maciej Soszka (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This article uses the inverse synthetic aperture radar (ISAR) imaging method to present real-world tests on 3-D radar imaging of noncooperative air targets. Initially, the fundamentals of 3-D ISAR are introduced. This is followed by a discussing of the challenges of obtaining high-quality 3-D radar images. An essential feature of the applied method is its basis on the back-projection family of techniques, eliminating the need for iterative image reconstruction. These theoretical concepts are validated using both simulations and real-life signals. This article also provides insights into the measurement campaign and the signal processing techniques applied to achieve the presented results.